Sexuality and Religious Court Authority: Interpreting Homosexuality in the Khulʿ Divorce Case in Singkawang, Indonesia - Anandya, Rivany; Ardiansyah; Hakim, Muhammad Lutfi (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2025)
Homosexuality, defined as same-sex relationships among men, is not explicitly recognized as a legal ground for divorce under Indonesian marriage law. This study examines how judges interpret homosexuality in divorce proceedings, focusing on a khulʿ case filed by a wife in the Religious Court of Singkawang, West Kalimantan, Indonesia. The case exposes a normative gap between formal legal provisions and the socio-religious realities encountered by Muslim women seeking legal protection. Employing a socio-legal approach and qualitative content analysis of Decision No. 134/Pdt.G/2025/PA.Skw as primary data, the research explores judicial reasoning within the frameworks of discretion and interpretive practice that connect statutory law, Islamic legal principles, and social context. The findings reveal that the judges intentionally characterized homosexuality as “deviant behavior” constituting ongoing marital discord (shiqāq). This reasoning integrates juridical references to statutory law and judicial precedents, theological arguments derived from Sūrat al-Rūm verse 21, and several qawāʿid fiqhiyyah (Islamic legal maxims) emphasizing harm elimination, alongside moral and social considerations that underscore divorce as a means to prevent greater harm. This study advances a theoretical framework of interpretive strategies that bridge normative gaps and illuminate how Islamic family law is adjudicated within the evolving socio-legal landscape of contemporary nation-states.